Hypertension-gut microbiota research trends: a bibliometric and visualization analysis (2000–2025) - Chen, Qilin; Ren, Chunzhen; Shu, Chang; Yang, Xue; Jiang, Hugang; Zhi, Xiaodong; Wang, Chunling; Liu, Kai; Zhao, Xinke; Li, Yingdong (Frontiers in Microbiology, 2025)
BackgroundHypertension is a major global public health challenge affecting over 1.3 billion people. Emerging evidence indicates that gut microbiota regulates blood pressure through metabolic and immune-inflammatory pathways. This provides novel insights into hypertension mechanisms and facilitates targeted interventions. However, research in this field faces three major challenges: (1) fragmented knowledge, (2) limited clinical translation, and (3) unclear developmental trajectories. Consequently, conventional reviews cannot adequately capture its dynamic evolution.ObjectiveUsing publications from the Web of Science Core Collection (2000–2025), we conducted a bibliometric analysis with CiteSpace and VOSviewer to map collaborative networks, analyze research hotspot evolution, identify emerging frontiers, and provide quantitative insights for field advancement.MethodsWe retrieved 2,827 qualified publications through Boolean logic search, then performed analyses including: annual publication trends, national/institutional/author collaboration networks, keyword co-occurrence and clustering, burst detection, and timeline/mountain range visualizations using CiteSpace and VOSviewer.ResultsPublication trends evolved through three phases: initial accumulation (annual output <50), accelerated growth, and stable maturation (250–450 annually). Driven by technology and clinical needs, China (918) and the US (676) led research, with networks involving Italy, Spain, etc. Academic institutions like the Univ. of Florida and Zhejiang Univ. were pivotal, and key teams (e.g., Yang Tao, Raizada Mohan K.) focused on mechanisms and translation. Research hotspots centered on “gut microbiota” and “blood pressure,” forming three modules: metabolic regulation, complication associations, and intervention strategies. Cluster analysis identified 10 groups—including short-chain fatty acids and TMAO—spanning basic to clinical research. Post-2017 foci like Akkermansia muciniphila, Mendelian randomization, and pulmonary hypertension signal a shift to precision mechanisms and personalized interventions.ConclusionThis study establishes a quantitative analytical framework for hypertension-gut microbiota research, revealing a collaborative landscape led by China and the United States with multidisciplinary integration. We identify metabolic reprogramming and microbiota-targeted interventions as core research priorities, providing theoretical foundations to address clinical translation barriers and advance precision medicine. Future research should strengthen cross-disciplinary collaboration, prioritize investigation of ethnicity-specific microbial signatures and microbiota-drug interactions, and accelerate clinical translation of targeted therapies.